Let a,m,n∈N. Show that if gcd(m,n)=1, then gcd(a,mn)=gcd(a,m)⋅gcd(a,n).
Proof:
Let u,v∈Z such that gcd(m,n)=um+vn=1. Let b,c∈Z such that gcd(m,a)=ab+cm. Let d,e∈Z such that gcd(a,n)=ad+en.
So gcd(a,m)⋅gcd(a,n)=a2bd+cmen+aben+emad.
Where do I go from here?
Answer
gcd(a,m)⋅gcd(a,n)=a(abd+ben+emd)+(mn)(ce)≥gcd(a,mn)
Say gcd(gcd(a,m),gcd(a,n))=p where p>1.
Then p|gcd(a,m) and p|gcd(a,n). Which means p|m and p|n. So p is a common divisor of m and n. gcd(m,n)≥p. But this is impossible since gcd(m,n)=1 and p>1. Thus, p=1
If gcd(a,m)=x, this means x|a and x|m. If x|m, then x|mn.
Thus x is a common divisor of a and mn. x|gcd(a,mn)
If gcd(a,n)=y, this means y|a and y|n. If y|n, then y|mn.
Thus y is a common divisor of a and mn. y|gcd(a,mn)
Because gcd(x,y)=1,xy|gcd(a,mn)
So gcd(a,m)⋅gcd(a,n)≤gcd(a,mn)
Therefore, gcd(a,m)⋅gcd(a,n)=gcd(a,mn)
No comments:
Post a Comment